Evaluasi Kelayakan Peserta Ujian Tulis Berbasis Komputer di SMK Cerdas Murni - Ratih Adinda Destari; Asbon Hendra Azhar; Wahyu Sapta Negoro; Charles Bronson Harahap; A Ardansyah (LPPM STIKOM Tunas Bangsa, 2023)
UTBK is a computer-based exam held several times a year whose scores can be used in the SBMPTN. At UTBK you are only allowed to take the test a maximum of 2 times, if after taking UTBK 2 times, participants can use the highest score between the 2 UTBK scores they have to register at PTN. UTBK consists of a Scholastic Potential Test (TPS) and an Academic Competency Test (TKA) where the test consists of a Science and Technology exam group and a Social and Humanitarian exam group which are designed to predict participants being able to complete their studies at higher education. A Decision Support System (DSS) is a computer-based system that can support decision making to solve semi-structured problems by utilizing existing data. Then it is processed into information in the form of suggestions, leading to a certain decision.